2020
DOI: 10.1002/cmdc.202000801
|View full text |Cite
|
Sign up to set email alerts
|

Tautomycetin Synthetic Analogues: Selective Inhibitors of Protein Phosphatase I

Abstract: Ser/Thr protein phosphatases (PPs) regulate a substantial range of cellular processes with protein phosphatases 1 (PP1) and 2 A (PP2A) accounting for over 90 % of the activity within cells. Nevertheless, tools to study PPs are limited as PPs inhibitors, particularly those selective for PP1 inhibition, are relatively scarce. Two examples of PP1‐selective inhibitors, which share structural similarities, are tautomycin (TTM) and tautomycetin (TTN). This work describes the development of PP1/PP2A inhibitors that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…3G ). These results clearly showed that PP2Acα plays an essential role in the virulence of T. gondii in mice, which may be related to the inhibition of extensive dephosphorylation ( 4 ), resulting in decreases in the abilities of invasion and proliferation.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…3G ). These results clearly showed that PP2Acα plays an essential role in the virulence of T. gondii in mice, which may be related to the inhibition of extensive dephosphorylation ( 4 ), resulting in decreases in the abilities of invasion and proliferation.…”
Section: Resultsmentioning
confidence: 85%
“…For instance, in contrast to them being only about 30% of the protein phosphatases in humans, serine/threonine (Ser/Thr) phosphatases account for approximately 80% of the protein phosphatome of Toxoplasma gondii , which is the most successful intracellular protozoan parasite, affecting almost all warm blooded animals and one-third world population ( 2 , 3 ). Ser/Thr phosphatase activities are mostly accomplished by protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A) in many eukaryotes, and these enzymes catalyze more than 90% of Ser/Thr phosphorylated protein reactions ( 4 ). However, although great efforts have been made toward elucidating the roles of Ser/Thr phosphatases in T. gondii and in other apicomplexan parasites ( 5 , 6 ), there is still a lack of comprehensive functional information on PP1 and PP2A in these important pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of naturally occurring small toxins capable of specifically inhibit PPs, largely contributed to the comprehension of Ser/Thr PPs role in various cellular events and other phosphorylation-dependent processes [ 12 , 13 , 14 ]. In fact, PPs are some of the most catalytically efficient enzymes, as they contain highly conserved active sites and do not possess high substrate specificity, which makes them very susceptible to inhibition by natural toxins [ 72 , 73 ]. Although most PP inhibitors present distinct chemical identities, they usually interact with a similar set of amino acids, along with the two metal ions they coordinate, that collectively compose the PP’s active site [ 12 , 74 ].…”
Section: Pp1 Pp2a and Pp2b Inhibition In Spermatozoamentioning
confidence: 99%
“…Over the last decade, there has been a particular interest and rebound in targeting the catalytic subunit of PP1 alone or as a holoenzyme. Given the low probability to develop a selective lead or drug acting against PP1 because of the high conservation of its active site within its family and across species, we and others examined strategies aiming to target PP1 regulatory sub-units to interrupt the formation of PP1 holoenzymes [ 56 , 58 , 61 , 121 , 131 , 132 , 133 ]. The feasibility of those strategies was supported by several studies carried out on viruses showing that the use of small molecules designed to bind to the non-catalytic RVxF binding site of PP1 [ 134 ] was able to prevent viral replication in vitro of viruses such as HIV1 and Ebola [ 135 , 136 , 137 ].…”
Section: Therapeutic Potential Of Protein Phosphatases As Drug Target...mentioning
confidence: 99%